Restoration and Resistance through Names: The Study of Naming Patterns among the Kirat Rai Community - Rai, Prakash (Kirat Pragya किरात प्रज्ञा, 2026)
This study explores how the name/ naming pattern among the Rai community of Nepal serves as a means of identity reclamation and resistance to state-sponsored homogenization in recent times. It focuses, in general, on Indigenous naming patterns and the Kirat Rai naming pattern, in particular, their transformation during the nation-state building process, and their revival as restoration and resistance to homogenization in the contemporary identity movement. By analyzing the naming pattern, socio-political contexts, and oral history/traditions, the study situates Kirat Rai names/naming pattern as powerful symbols in the struggle for ethnic recognition, cultural survival, and reclaiming their vulnerable identity in recent days. It is the everyday form of resistance (Scott, 1985) to the nation-state building process in general, and homogenization/assimilation, in particular.